The Effect of Using Ramps with Trench Cylindrical Holes on Film Cooling Effectiveness - Ahmed A. Imram; Humam K. Jalghef; Falah F. Hatem (Wasit Journal of Engineering Sciences)
The effect of introducing ramp with a cylindrical slot hole on the film cooling effectiveness has been investigated experimentally and numerically. The film cooling effectiveness measurements are obtained experimentally. A test study was performed at a single mainstream with Reynolds number 76600 at three different coolant to mainstream blowing ratios 1.5, 2, and 3. Numerical simulation is introduced to primarily estimate the best ramp configurations and to predict the behavior of the transport phenomena in the region linked closely to the interaction between the coolant air injection and the hot air mainstram flow. The results showed that using ramps with trench cylindrical holes would enhanced the overall film cooling effectiveness by 83.33% compared with baseline model at blowing ratio of 1.5, also  the best overall flim cooling effectevness was obtained at blowing ratio of 2 while it is reduced at blowing ratio of 3.